(untitled) (The Review of Diabetic Studies, 2025)
The current research emphasizes the synthesis, structural identification, and pharmacophoric assessment of a new nitro-substituted heterocyclic compound referred to as 4r. The main aim of this study was to incorporate an electron-withdrawing nitro functional group into a heterocyclic framework to explore its structural impact and pharmacophoric significance at the molecular level. Compound 4r was effectively synthesized via a cyclization method driven by condensation under regulated reaction conditions. The structural confirmation of the synthesized compound was achieved through multiple spectroscopic methods, such as Infrared (IR) spectroscopy, Proton Nuclear Magnetic Resonance (¹H NMR), Carbon-13 Nuclear Magnetic Resonance (¹³C NMR), and elemental analysis. Spectral data confirmed the existence of important functional groups including the nitro group, carbonyl connection, and aromatic structure. Pharmacophoric assessment indicated the existence of notable molecular characteristics such as hydrogen bond acceptors, electron-withdrawing sites, and aromatic interaction regions, all of which enhance its interaction capacity at the molecular level.